The Creek - Newman, Shirlee Petkin (New York : Franklin Watts, 1996)
Discusses the history, culture, and daily life of the Creek Indians.
Includes bibliographical references (p. 60) and index.
Keywords: Creek Indians -- Juvenile literature; Creek Indians; Indians of North America